Transcriptomic responses of sponge holobionts to in situ, seasonal anoxia and hypoxia - Strehlow, Brian W.; Schuster, Astrid; Francis, Warren R.; Eckford-Soper, Lisa; Kraft, Beate; McAllen, Rob; Nielsen, Ronni; Mandrup, Susanne; Canfield, Donald E. (Peer Community Journal)

(untitled)
Deoxygenation can be fatal for many marine animals; however, some sponge species are tolerant of hypoxia and anoxia. Indeed, two sponge species, Eurypon sp. 2 and Hymeraphia stellifera, survive seasonal anoxia for months at a time. To understand their tolerance mechanisms, we performed differential gene expression analyses on the sponges, their mitochondria and their microbial symbionts under in situ conditions of normoxia, hypoxia and anoxia. Each species possessed a unique microbiome, but the microbiomes of each species were dominated by a species-specific Thaumarchaeon and a Gammaproteobacterium. Holobiont gene expression was species-and oxygen-level dependent, though there were some shared interspecific responses to deoxygenation. In general, few changes occurred in the expression of sponge metabolic genes as a function of oxygenation level, indicating that they may remain metabolically active under anoxia. However, ATP synthesis genes were significantly upregulated under hypoxia when compared to normoxia, and genes for DNA replication were downregulated. Mitochondrial gene expression was effectively unchanged under both hypoxia and anoxia. Nevertheless, both anoxia and hypoxia caused upregulation of heat shock proteins (HSPs), indicating cellular level adaptations to deoxygenation stress. A meta-analysis demonstrated that sponge transcriptional responses to anoxia were distinct from those displayed by other invertebrates while dormant, and the hypothesis of sponge dormancy under anoxia was not supported. Thaumarchaeota symbionts also upregulated stress response genes in hypoxia, while maintaining expression of oxygen-dependent metabolic pathways under hypoxia and anoxia. Gammaproteobacteria symbionts showed relatively few noteworthy changes in gene expression in response to anoxia but decreased metabolic gene expression in hypoxia. There was no clear evidence of upregulated anaerobic respiration in the transcriptomes of the sponge holobionts under anoxia or hypoxia. The tolerance of some sponges to prolonged anoxia warrants further investigation and could give them an advantage in future oceans following climate change as well as in ancient oceans when oxygen concentrations were lower than at present.